Pragmatism in Learning Negotiation Texts: A Philosophical Analysis of Indonesian Language Teaching Modules for TJKT Vocational High School Students - Auliyah Niswa; Anas Ahmadi (Continuous Education: Journal of Science and Research, 2026)
The teaching of negotiation texts in Indonesian language learning at Vocational High Schools plays a crucial role in developing students’ communicative competence for the workplace; however, classroom practices tend to remain academically oriented and emphasize textual structure rather than functional and contextual language use. This study aims to analyze the Indonesian language negotiation text teaching module for Grade X students of the Computer and Telecommunications Network Engineering program from a pragmatist perspective, particularly in relation to principles of experiential learning, action-based learning, and problem-solving. This research employed a qualitative descriptive approach, with data collected through document analysis of the teaching module, interviews with Indonesian language teachers, and classroom observations of module implementation. The analysis focused on four main components of the module: learning objectives, learning materials, learning activities, and learning assessment. The findings indicate that the negotiation text module has not consistently reflected pragmatist principles. The learning objectives remain oriented toward normative academic achievement, the learning materials are general and insufficiently contextualized to the workplace environment, learning activities are dominated by writing tasks with limited opportunities for authentic communicative action, and assessment practices primarily focus on written products rather than the negotiation process and communicative strategies. These results suggest that negotiation text learning risks losing its meaningfulness for vocational students, highlighting the need for the development of teaching modules that are more contextual, functional, and aligned with real-world vocational communication demands.